Current status and potentials of enhanced geothermal system in the Eastern Pontide Orogenic Belt, Turkey - Şener, Mehmet Furkan (Center of Biomass & Renewable Energy (CBIORE), 2024)
The radioactive decay of isotopes is one of the most important sources of heat in the Earth's interior. The main radiogenic elements in the crust are U, Th, and K in granitoids. Radiogenic granites are becoming increasingly important as they support the development of the renewable energy sector. This study provides an in-depth review of the development of Enhanced Geothermal Systems (EGS) technology. Many countries, such as France and the UK, have initiated and contributed to energy production using EGS technology. In addition, this study calculates the potential production capacity of radiogenic granites in the Eastern Pontide Oraganic Belt (EPOB) and assesses their significant contribution to the Turkish economy in line with the Sustainable Development Goals (SDGs). The total area of radiogenic granites within the EBOP is 7116.35 km2 and these granites contain average concentrations of U 3.25 ppm, Th 16.44 ppm, and K 3.7%. The plutons studied can generally be classified as medium to low heat producing granitoids. Ayeser, Camiboğazı, and Ayder (3.36-6.98 µW/m3), which are close to the average heat production value of the continental crust (5 μW/m3), may be suitable areas for EGS. Currently, EBOP granites have the capacity to produce 61 x 109 kWh of electricity. In addition to electricity, heat from granites can be used for other applications such as space heating and greenhouse cultivation.